2017
DOI: 10.3389/fimmu.2017.01484
|View full text |Cite
|
Sign up to set email alerts
|

CD40L Expression Allows CD8+ T Cells to Promote Their Own Expansion and Differentiation through Dendritic Cells

Abstract: CD8+ T cells play an important role in providing protective immunity against a wide range of pathogens, and a number of different factors control their activation. Although CD40L-mediated CD40 licensing of dendritic cells (DCs) by CD4+ T cells is known to be necessary for the generation of a robust CD8+ T cell response, the contribution of CD8+ T cell-expressed CD40L on DC licensing is less clear. We have previously shown that CD8+ T cells are able to induce the production of IL-12 p70 by DCs in a CD40L-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 44 publications
2
31
1
Order By: Relevance
“…CD154 + CD8 T cells (also called CD8 helper cells) have been shown to support their own expansion and differentiation and to activate dendritic cells to promote antitumor immunity. 33 Although the RhoC 20mer contains an embedded HLA-A*03 binding peptide, we did not observe any CD8 T cell response (one single time point tested) in the two patients carrying the HLA-A*03 allele. 23 Since epitope spreading was shown to be associated with a better clinical outcome, 34 we also tested CD8 T cell reactivities against epitopes derived from PCa-associated antigens (PSA, PSMA, prostein, TRPP8 and survivin) in five HLA-A*02 patients.…”
Section: Discussioncontrasting
confidence: 52%
“…CD154 + CD8 T cells (also called CD8 helper cells) have been shown to support their own expansion and differentiation and to activate dendritic cells to promote antitumor immunity. 33 Although the RhoC 20mer contains an embedded HLA-A*03 binding peptide, we did not observe any CD8 T cell response (one single time point tested) in the two patients carrying the HLA-A*03 allele. 23 Since epitope spreading was shown to be associated with a better clinical outcome, 34 we also tested CD8 T cell reactivities against epitopes derived from PCa-associated antigens (PSA, PSMA, prostein, TRPP8 and survivin) in five HLA-A*02 patients.…”
Section: Discussioncontrasting
confidence: 52%
“…In order to gain insight into the role of CD4 T cells on CTL activation, we studied the pathways by which CTL responses are triggered. One of the principal mechanisms by which CD4 T cells help the CTL cells priming is via licensing of DCs through the CD40-CD40L interactions, leading to maturation of DCs prior to their priming of CD8 T cells (43). In the absence of CD4 T cells, CD40 signaling can substitute the otherwise required T-helper signals, and the administration of agonistic anti-CD40 antibodies can improve vaccine efficacy in CD4 T-cell deficient conditions (34).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of CD4 T cells, CD40 signaling can substitute the otherwise required T-helper signals, and the administration of agonistic anti-CD40 antibodies can improve vaccine efficacy in CD4 T-cell deficient conditions (34). Moreover, a subset of CD8 T cells can express CD40L allowing an autocrine activation of CD8 T cells independent of T-helper cells (43). In the current study, we showed that PCI-based vaccination was CD4 T-cell independent, but that the T-helper signals were not substituted by CD40 signals, since CD8 T-cell responses were not impaired in CD40L-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…CD1a is a marker of DCs and the double phenotypes of CD1a and CD40 used in the present study are specific DC markers. Furthermore, CD40+ staining indicates that DCs are in the mature phase and interacting with the T cells ( 11 ). The results of the present study indicate that the number of DCs in nITM tissue is significantly lower compared with NP tissues, which is consistent with previous reports ( 12 ) and suggests that DCs may serve an important role in the onset and development of NP.…”
Section: Discussionmentioning
confidence: 99%